Washover Fan Evolution, Assateague Island National Seashore, MD (2012-2019) - Lecompte, Karley (East Carolina University, 2021)
Washover fans are coastal geomorphological features found on barrier islands. These features often help aid with barrier island landward migration. Within the scientific community, research is often based around pre- and post- storm data. However, in this study we analyze fan data between 2012-2019. The 2012-2017 LiDAR data was downloaded from NOAA Data Access Viewer, while the most recent 2019 data was collected by East Carolina University’s research team using a Phantom 4 Pro drone. The imagery collected by the UAV were processed in Agisoft Metashape Pro and ArcMap Desktop. Both sites were observed for evolutionary traits within themselves and between one another. Similarities in topographic raising and lowering were found, as well as sediment build up at the fan’s lateral extents, wedge-like fan, rectangular and V-shaped channels, and a flattening of the overall surface. The human impacted 75 fan from the berm construction project also followed similar patterns as the 85 natural fan. The information gained by this study can help inform the NPS staff how fast and large the fan is growing with time. This thesis research helped identify evolutionary traits of washover fans through time and should be compared to other fans located in distant locations for further analysis.
Keywords: Overwash; SfM; Washover fans--Maryland; Barrier islands--Maryland; Ocean waves--Maryland; Assateague Island National Seashore (Md. and Va.)